2022
DOI: 10.18103/mra.v10i9.2986
|View full text |Cite
|
Sign up to set email alerts
|

The Apportionment of Pharmacogenomic Variation: Race, Ethnicity, and Adverse Drug Reactions

Abstract: Fifty years ago, Richard Lewontin found that the vast majority of human genetic variation falls within (~85%) rather than between (~15%) racial groups. This result has been replicated numerous times since and is widely taken to support the notion that genetic differences between racial groups are trivial and thus irrelevant for clinical decision-making. The aim of this study was to consider how the apportionment of pharmacogenomic variation within and between racial and ethnic groups relates to risk disparit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…This is consistent with the notion that race and ethnicity are purely social constructs with little or no biological significance [42]. Here, it must be reiterated that observed patterns of pharmacogenomic variation, particularly as they relate to adverse drug reactions, clearly support the clinical relevance of race and ethnicity [21,22,24,25]. In fact, we previously showed that when pharmacogenomic variation is partitioned exactly in the way that Lewontin and others have described, 85% within-group variation and 15% between-group variation, there can be up to 700 excess adverse drug reactions per 1000 patients predicted for the recessive effect mode and as many as 300 adverse reactions predicted for the dominant mode [24].…”
Section: Adverse Drug Reactionssupporting
confidence: 83%
See 3 more Smart Citations
“…This is consistent with the notion that race and ethnicity are purely social constructs with little or no biological significance [42]. Here, it must be reiterated that observed patterns of pharmacogenomic variation, particularly as they relate to adverse drug reactions, clearly support the clinical relevance of race and ethnicity [21,22,24,25]. In fact, we previously showed that when pharmacogenomic variation is partitioned exactly in the way that Lewontin and others have described, 85% within-group variation and 15% between-group variation, there can be up to 700 excess adverse drug reactions per 1000 patients predicted for the recessive effect mode and as many as 300 adverse reactions predicted for the dominant mode [24].…”
Section: Adverse Drug Reactionssupporting
confidence: 83%
“…Here, we briefly review examples of pharmacogenomic differences among racial and ethnic groups from our own work in the US, the UK, and Colombia [21][22][23][24][25]. Most recently, we used population biobanks to interrogate the relationship between race, ethnicity, and pharmacogenomic variation in the US and the UK [25].…”
Section: Race Ethnicity and Pharmacogenomic Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, HLA-A has been observed to be most frequently associated with SJS/TEN reactions induced by the AEDs carbamazepine, lamotrigene, phenytoin, and zonisamide, followed by HLA-B or C subtypes [26]. Furthermore, ethnicity has a role to play in the type of reaction observed [27]. Pharmacogenomic considerations such as HLA subtype can be used to guide dose adjustments or drug selections to avoid any life-threatening ACDRs [28].…”
Section: Pathogenesis: Mechanism and Risk Factorsmentioning
confidence: 99%